(untitled) (Amsterdam, 2012)
The UX Book: Process and Guidelines for Ensuring a Quality User Experience aims to help readers learn how to create and refine interaction designs that ensure a quality user experience (UX). The book seeks to expand the concept of traditional usability to a broader notion of user experience; to provide a hands-on, practical guide to best practices and established principles in a UX lifecycle; and to describe a pragmatic process for managing the overall development effort.
Giao diện người - máy
Keywords: Giao diện người dùng (hệ thống máy tính),User interfaces (Computer systems)